PENINGKATAN PERAN KEPALA SEKOLAH SEBAGAI SUPERVISOR MELALUI BIMBINGAN BERKELANJUTAN DI GUGUS KI HAJAR DEWANTARA UPT DINAS PENDIDIKAN KECAMATAN KLEDUNG - Dahono Dahono (Universitas PGRI Semarang, 2015)
Most of the Principal in carrying out the preparation of Supervision Program is still low, in carrying out their supervision activities are not preceded by good planning so impressed origin implement. The aim of the research is to improve Peren principal as supervisor, especially in the preparation program through the guidance of continuous supervision.The subjects were seven principals of research carried out in the second semester of academic year 2014/2015, the hope in the school year 2015/2016 school principals in implementing the supervision starting from the preparation of the program so that the implementation goes according to plan in advance so that already obtained results in an optimal supervision.This research was conducted in two cycles, the first cycle is carried out through the guidance of the group obtained an increase in the average value of the programming supervision of 42.85% compared to the initial conditions. The second cycle of the guidance implemented individually acquired 14.29% increase compared to the first cycle, or at the end of the second cycle there is a 57.14% increase compared to the initial state or the final result of 71.43% according to performance indicators